2D Layered Double Hydroxide Nanoparticles: Recent Progress toward Preclinical/Clinical Nanomedicine. Issue 2 (20th August 2019) - Cao, Zhenbang; Li, Bei; Sun, Luyao; Li, Li; Xu, Zhi Ping; Gu, Zi
Abstract: 2D nanomaterials represent one of the next‐generation biomaterials with versatile physicochemical advantages that allow for diverse biomedical applications in disease diagnosis, prevention, and treatment. In particular, layered double hydroxide (LDH) nanoparticles, as a typical 2D nanomaterial, have recently shown unprecedented advances in controllable and simplified chemical construction, versatile surface engineering, and comprehensive biological investigation. To realize in vivo biomedical applications, recent efforts have been substantially devoted to a few critical aspects of LDH nanomedicine including nanoparticle stability in physiological environments, accumulation at the disease‐targeted site, selective biological response to the nanoparticle, systematic biosafety examination, integration with multiple diagnostic and therapeutic modalities, and the adjuvant activity and suitability for gene‐based and protein‐based vaccines, which are herein comprehensively reviewed. The challenges and future development strategies of LDH nanomedicine are also discussed toward practical biomedical applications to benefit patients. Abstract : 2D layered double hydroxide (LDH) nanoparticles with tunable structures are developed for a diverse range of in vivo biomedical applications to achieve enhanced diagnostic/therapeutic efficiency and minimized systemic toxicity. The use of LDH nanoparticles to address the critical issues that practical nanomedicine faces is discussed together with challenges and perspectives.